Evaluation of Predictors of Biochemical Recurrence in Prostate Cancer Patients, as Detected by 68Ga-PSMA PET/CT - Mads T. Christensen; Mads R. Jochumsen; Søren Klingenberg; Karina D. Sørensen; Michael Borre; Kirsten Bouchelouche (Diagnostics, 2022)
Objectives: To explore the existence of new predictors of the 68Ga-Prostate-Specific Membrane Antigen (PSMA) PET/CT detection rate at biochemical recurrence (BCR) and to determine the detection rate of 68Ga-PSMA PET/CT dependent of prostate-specific antigen (PSA) levels. Materials and methods: In total, 189 PCa patients scanned with 68Ga-PSMA PET/CT for detection of BCR after curatively intended treatment with either radical prostatectomy (n = 153) or radiotherapy (n = 36) were included. Clinicopathological information at the time of diagnosis (PSA, clinical tumor-stage, International Society of Urological Pathology Grade Group and whether 68Ga-PSMA PET/CT was used for primary staging), treatment (RT/RP and histopathology of the prostatectomies), and pre-PET PSA were collected from medical records. Results: Of the 189 68Ga-PSMA PET/CT scans, 103 (54.5%) were positive for BCR of PCa. No significant coherency was observed between detection rate and any clinicopathological variables at diagnosis. Detection rates significantly increased with rising PSA: <0.5 ng/mL = 28%, 0.5 ≤ 1 ng/mL = 39%, 1 ≤ 2 ng/mL = 64%, 2 ≤ 5 ng/mL = 87.5% and ≥5 ng/mL = 97%. Conclusions: The detection rate of PCa recurrence was strongly dependent of pre-PET PSA levels. None of the additional clinical variables acquired during primary staging, prostatectomy pathology reports, nor primary staging imaging modality affected the detection rate.